Food Web Connectivity in a Mangrove–Seagrass–Patch Reef (MSP) Seascape: Lessons from a Tropical Back-Reef in Puerto Rico - Antonietta Quigg; R. J. David Wells; Jay R. Rooker; Ronald L. Hill; Larissa L. Kitchens; Michael A. Dance; David L. Moulton; Phillip J. Sanchez; Beatrice Padovani Ferreira (Fishes, 2023)
Alterations to the functions and connectivity of mangrove–seagrass–patch reef (MSP) seascapes have the potential to impact the survival, foraging activities, and movement of reef-dependent invertebrates (e.g., crabs and shrimp) and fishes. In the current study, we examined carbon flow in the Guánica Biosphere Reserve in southwestern Puerto Rico using pigment analysis of particulate organic matter and stable isotope analysis of carbon (δ13C) and nitrogen (δ15N) in flora and fauna. Several lines of evidence pointed to N2 fixers (cyanobacteria) being important for fueling primary productivity in this oligotrophic ecosystem including low (<0.7 µg L−1) chlorophyll, prevalence of cyanobacteria based on pigment signatures, and the isotope signatures of seagrass and red mangrove leaf tissue (enriched δ15N values) and consumers (depleted δ15N values). Food web mixing models based on stable isotopes (δ13C and δ15N) revealed that multiple producers (phytoplankton, benthic microalgae, seagrasses, etc.) contributed organic matter to the consumers (zooplankton, invertebrates, and fishes) in the MSP seascape at the center of the reserve. Contribution estimates for common benthic invertebrates (crabs and shrimp) were taxon-specific, and the highest input was generally linked to particulate organic matter (POM) and benthic microalgae (BMA)/seagrass producer categories, although meaningful mangrove contribution was observed for some taxa. Similarly, contribution estimates for fishes were highest for POM and BMA/seagrass, with the latter producer category being more important for species known to migrate from mangroves or patch reefs to seagrass beds at night (bluestriped grunt, French grunt, and white grunt). Although all fish investigated were observed in mangrove prop-root habitats, input of organic matter from mangroves to these consumers was typically limited for most of the species examined. Understanding these complex seascapes contributes to our understanding of the ecology of these vital ecosystems.